Biodiversity‐ecosystem functioning relationships in a long‐term non‐weeded field experiment - Veen, G. F.; Putten, Wim H.; Bezemer, T. Martijn (Ecology (Durham), 2018)
Many grassland biodiversity experiments show a positive relationship between biodiversity and ecosystem functioning, however, in most of these experiments plant communities are established by sowing and natural colonization is prevented by selective weeding of non‐sown species. During ecosystem restoration, for example on abandoned fields, plant communities start on bare soil, and diversity is often manipulated in a single sowing event. How such initial plant diversity manipulations influence plant biodiversity development and ecosystem functioning is not well understood. We examined how relationships between taxonomic and functional diversity, biomass production and stability develop over 16 yr in non‐weeded plots sown with 15 species, four species, or that were not sown. We found that sown plant communities become functionally similar to unsown, naturally colonized plant communities. However, initial sowing treatments had long‐lasting effects on species composition and taxonomic diversity. We found only few relationships between biomass production, or stability in biomass production, and functional or taxonomic diversity, and the ones we observed were negative. In addition, the cover of dominant plant species was positively related to biomass production and stability. We conclude that effects of introducing plant species at the start of secondary succession can persist for a long time, and that in secondary succession communities with natural plant species dynamics diversity–functioning relationships can be weak or negative. Moreover, our findings indicate that in systems where natural colonization of species is allowed effects of plant dominance may underlie diversity–functioning relationships.